Adsorption behavior of PB(II) onto xanthated rubber (Hevea brasiliensis) leaf powder - Wan Mohd Khalir, Wan Khaima Azira; Megat Hanafiah, Megat Ahmad Kamal; Mat So'ad, Siti Zaiton; Wan Ngah, Wan Saime (Versita, Warsaw, 2011)
A plant waste, rubber (Hevea brasiliensis) leaf powder was modified with carbon disulfide (xanthation) for the purpose of introducing sulfur groups, and the adsorbent performance in removing Pb(II) ion was evaluated. Pb(II) adsorption was confirmed by spectroscopic analysis, which involved Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The amount of Pb(II) adsorbed increased with increasing pH, contact time and concentration but slightly decreased with increasing ionic strength. Adsorption equilibrium was achieved in less than 60 min and followed the pseudo-second order model. The isotherm data indicated that Pb(II) adsorption on xanthated rubber leaf (XRL) fitted well with Langmuir isotherm model. The maximum adsorption capacity computed from the Langmuir isotherm model was 166.7 mg/g. Pb(II) adsorption occurred via ion-exchange and complexation mechanisms.